How the brand identity of the Holy Crab was improved through social media marketing by Chromatic Limited - Hassan, Emad Bin Mohammad (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.